Spectroscopic and magnetic properties of two di-copper(II) complexes with macrocyclic Schiff bases - Dziembowska, T.; Guskos, N.; Typek, J.; Szymczak, R.; V. Likodimos; Glenis, S.; Lin, C.L.; Wabia, M.; Jagodzinska, E.; Fabrycy, E. (Materials Research Bulletin, 1999)
Two binuclear copper(II) complexes with macrocyclic Schiff bases Cu2LI(CH3COO)2·5H2O (complex I) and Cu2LII(CH3COO)2·2H2O (complex II) were synthesized and then characterized by IR, UV, and thermogravimetric analysis (TGA) measurements. TGA was used to investigate the desolvation of lattice water molecules. IR spectra demonstrated the formation of the cyclic compound and together with chemical elemental analysis were used to propose the structure of the complexes. The UV spectra of both complexes are typical for binuclear copper(II) complexes with Robson-type ligands. Variable-temperature magnetic susceptibility measurements corroborated by EPR and low-temperature isothermal magnetization data confirmed the formation of copper dimers with antiferromagnetic exchange coupling constants of -400 and -1250 cm-1 for complexes I and II, respectively, residing outside the usual range for the phenoxide bridged Cu(II) complexes. This implies the possibility that additional superexchange paths through the macrocyclic ligand may affect the intradimer exchange interaction as well as the phenoxide oxygen bridges.